Investigating How Peer Interaction Dynamics Shape Children’s Cognitive Problem-Solving Abilities - Aulia Rahmah, Nissa; Undayasari, Dwi; Asri Aulia, Siti; Putri Raisya, Safina (Jurusan Pendidikan Islam Anak Usia Dini, 2025)
Early childhood is a pivotal stage in the developmental process, including cognitive and social development. At this stage, their high curiosity encourages them to start interacting with their peers. This interaction plays a pivotal role in helping children understand their environment while developing their thinking skills, especially in problem solving. This study aims to determine the effect of interaction with peers on children's thinking in problem solving. The study uses a qualitative method with an observational approach, observing children's behaviour when playing alone and with peers. The focus of observation includes how children play, interact, and respond to problems. The results of the study show significant differences between children who actively interact with peers and those who interact less. Children who frequently interact tend to understand mistakes more quickly and are able to solve problems appropriately. Conversely, children who rarely interact show difficulty in understanding mistakes and solving problems in ways that are less in line with the teacher's instructions.